Affecting behavioural change through empowerment: conceptual insights from theory and agricultural case studies in South Asia - Serena H. Hamilton; Wendy S. Merritt; Lucy Carter; Arnab Chakraborty; Michaela Cosijn; Lilly Lim-Camacho; Rajeshwar Mishra; Geoff Syme; Mahanambrota Das; Dhananjay Ray (Regional Environmental Change, 2022)
Affecting behavioural change is a common underlying goal across environmental and agricultural sciences, from climate change mitigation and adaptation, biodiversity conservation, water management, to crop diversification. However, many projects fail to drive or sustain change despite sound science and good intentions. This paper draws on existing theories of behavioural change to construct a conceptual framework that explores pathways to initiate and sustain change through the lens of empowerment, self-efficacy and agency. The framework is demonstrated with case studies from a project in India and Bangladesh that examined social inclusion of marginalised and poor farmers in the context of intensifying agriculture. The framework and case studies highlight that a number of conditions are needed to affect meaningful change including that target beneficiaries are suitably motivated, believe in their own capability and power to enact change and have access to the necessary resources. We propose the framework as a tool to help project teams explore the underlying elements of the process of change when designing, implementing and assessing agricultural or environmental projects and interventions. We contend that behavioural and social change needs to be explicitly fostered in such endeavours to achieve better and longer-term outcomes for the people and environment.

Knowledge that Acts: Evaluating the Outcomes of a Knowledge Brokering Intervention in Western Australia’s Ningaloo Region - Kelly Chapman; Fabio Boschetti; Elizabeth Fulton; Pierre Horwitz; Tod Jones; Pascal Scherrer; Geoff Syme (Environmental Management, 2017)

Comparing irrigation management reforms in Australia and India – a special reference to participatory irrigation management - Rajendra Poddar; M Ejaz Qureshi; Geoff Syme (Irrigation and Drainage, 2011)
Efficient irrigation water management has become a common goal for continued growth and sustainable development in both India and Australia. The two countries have followed definite paths for achieving the best irrigation management policy. Australia has adopted irrigation management transfer (IMT) with emphasis on privatisation, while India has focused on participatory irrigation management (PIM). Australia and India have adopted these approaches in one of their main river basins, namely the Murray‐Darling Basin (MDB) and the Krishna Basin, respectively. Institutional reforms in irrigation management in the MDB developed independently of global progress in IMT as compared to the Krishna Basin where the reforms were imposed from the top. Further, irrigation management entities in the MDB, either under public or participatory domain, relied heavily on market‐based instruments to achieve efficiency in irrigation water management. In contrast, PIM in the Krishna Basin in India appears to be an experiment with command and control in diverse legal and organisational settings across time and space. In summary, in terms of the parameters chosen in their nearest proximity to measure performance, the Australian IMT programme seems to have performed better than the Indian PIM programme. Copyright © 2009 John Wiley & Sons, Ltd.